Comparison of the hybrid and partial stent-in-stent method for endoscopic three-segment drainage for unresectable malignant hilar biliary obstruction - Yoshinari, Motohiro; Hijioka, Susumu; Nagashio, Yoshikuni; Maruki, Yuta; Ohba, Akihiro; Kawasaki, Yuki; Takeshita, Kotaro; Morizane, Chigusa; Tanaka, Yasuhito; Okusaka, Takuji (Endoscopy International Open, 2023)
Background and study aims The clinical outcome of the new hybrid drainage method for unresectable malignant hilar biliary obstruction (UMHBO) has not yet been compared with that of the partial stent-in-stent (PSIS) method with three or more stents.Patients and methods Patients with UMHBO underwent drainage of three segments using the hybrid or PSIS method. The clinical outcomes of both methods were compared retrospectively.Results Overall, 54 patients underwent the hybrid (n = 31) or PSIS (n = 23) method of drainage with three or more stents for UMHBO. There were no significant differences in the technical success rate (hybrid vs. PSIS, 87.1 % vs. 87 %), clinical success rate according to per-protocol analysis (81.5 % vs. 70 %), early adverse events rate (14.8 % vs. 10%), late adverse events rate (7.4 % vs. 0 %), and technical success rate of the endoscopic transpapillary reintervention (90.9 % vs. 100 %). Time to recurrent biliary obstruction (TRBO) of the hybrid and PSIS methods was 178 and 231 days, respectively, with no significant difference (P = 0.354).Conclusions The choice between the two methods should be made at the physician’s discretion.